A sociological study of children with albinism at a special school in the Limpopo province - R.J. Gaigher; P.M. Lund; E. Makuya (AOSIS, 2002)
This article maintains that it is the social context, as much as, and sometimes more than the physical condition, that largely structures and limits the lives of people with albinism. It deals with albinism from a sociological, rather than a medical perspective. Viewed as such the problems experiencing by affected people stem primarily not from their physical differences but from the way others respond to those differences and from the social and physical environments they have to cope with. The article is based on a study of 32 children with albinism from a special school in the Limpopo province. Educational, health and social problems, attitudes and perceptions about albinism were tested by way of structured interviews. The data reveal an acute lack of information about the causes and consequences of albinism. It projects it as a condition still deeply immersed in myths and superstition resulting in the stigmatising and rejection of affected people. It also discloses a physical environment which is preventing rather than supporting people with albinism from reaching their potential. It calls for a reorientation in dealing with albinism -away from just medical intervention to treating it as a social construct requiring a holistic approach.